2001
DOI: 10.1021/jf010379o
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Tryptophan with Carbohydrates:  Mechanistic Studies on the Formation of Carbohydrate-Derivedβ-Carbolines

Abstract: Numerous carbohydrate-derived beta-carbolines have been identified for the first time in model reactions of tryptophan with glucose and ribose, as well as in food samples. Extending these structural studies, we performed detailed investigations to elucidate the corresponding intermediates and formation pathway of these alkaloids. Degradation experiments with purified tryptophan glycoconjugates established that only glyco-tetrahydro-beta-carboline-3-carboxylic acids, and not the N-glycosides nor the C-glycoconj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…42 According to Wang, the formation of compounds 14 and 15 from tryptophan and xylose, involves a sequence including Pictet-Spengler condensation, oxidative decarboxylation, tautomerization, and dehydrogenation steps, a mechanism in which isomerization of the sugarderived side chain at C-1' is essential. The use of glucose as model sugar allowed confirmation of the side chain isomerization feature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 According to Wang, the formation of compounds 14 and 15 from tryptophan and xylose, involves a sequence including Pictet-Spengler condensation, oxidative decarboxylation, tautomerization, and dehydrogenation steps, a mechanism in which isomerization of the sugarderived side chain at C-1' is essential. The use of glucose as model sugar allowed confirmation of the side chain isomerization feature.…”
Section: Methodsmentioning
confidence: 99%
“…A special class of isoquinoline alkaloids, which includes the widely known emetine from Cephaelis ipecacuanha can be formed by with dopamine (42) and related compounds.…”
Section: Scheme 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their importance to the food industry, the interaction of amino acids and sugars has been studied extensively [4][5][6][7][8][9]. Many of these studies focused on conditions that favor or reduce browning reactions [10,11], while others focused on the formation of specific products and the underlying reaction mechanisms [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…22 Many researches demonstrated that the enzymatic Pictet-Spengler reaction, catalyzed by Pictet-Spenglerase, was one of the characteristics of b-carboline alkaloid biosynthesis. [23][24][25] Feeding experiments with 5-F-Trp and 13 C labeled glucose and acetate revealed that the synthesis of b-carboline involved a Pictet-Spengler cyclization, a decarboxylation and C-ring oxidation process. 26,27 Combining of the published literatures and basic organic synthesis mechanism, the biosynthetic pathway of compounds 1-3 were proposed.…”
Section: Proposed Biosynthetic Pathwaymentioning
confidence: 99%